PENGARUH MODEL PEMBELAJARAN PROBING PROMPTING BERBANTUAN MEDIA QUESTION CARD TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS III SD - Nadia Sarianti; Allen Marga Retta; Puji Ayurachmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Probing Prompting learning model assisted by Question Card media on the critical thinking skills of Grade III elementary school students. This research is an experimental study with a quantitative experimental research design. The population in this study consisted of 164 students at SD Negeri 226 Palembang. The sample was selected using purposive sampling technique, with Class III.4 (32 students) as the experimental group applying the Probing Prompting learning model assisted by Question Card media, and Class III.5 (32 students) as the control group using conventional learning methods. The data collection technique employed was a test designed to measure students’ critical thinking skills, while the data analysis used the independent sample t-test. The results of this study indicate that there is a significant effect of the Probing Prompting learning model assisted by Question Card media on improving the critical thinking skills of Grade III elementary school students. Students in the experimental class demonstrated enhanced analytical thinking, greater engagement during learning activities, and improved performance in problem-solving tasks compared to those in the control class. These findings suggest that incorporating the Probing Prompting learning model with Question Card media can be an effective strategy for fostering critical thinking skills in elementary mathematics education.